Pengaruh Promosi Dan Kualitas Pelayanan Terhadap Kepuasan Pengunjung Dengan Keputusan Pengunjung Sebagai Variabel Intervening Pada Objek Wisata Candi Borobudur Kabupaten Magelang - Maulida Purnamasari; Agung Budiatmo (Jurnal Ilmu Administrasi Bisnis, 2019)
Quality tourism objects are indicated by the number of tourists visiting increasing every year. Based on the data of visitors to the Borobudur Temple, it can be seen that there has been a relative decline over the past few years. From these problems, it can be seen that there are indications of a decrease in visitor decisions caused by promotion and service quality. Thus, the declining visitor's decision then affects the decline in visitor satisfaction. This research is a type of explanatory research with a quantitative approach. Sampling using purposive sampling technique with incidental sampling so that found 122 respondents who are visitors to the Borobudur Temple. The technique of collecting data using questionnaires and documentation. This study uses quantitative analysis with validity, reliability, correlation coefficients, coefficient of determination, regression analysis, t test and F test with the help of IBM SPSS version 25.0 program and two-stage regression analysis to test the effect of intervening variables. Based on the results of the study indicate that promotion and service quality partially have a significant effect on visitor decisions, visitor decisions have a significant effect on visitor satisfaction. The visitor's decision can mediate the effect of promotion on satisfaction as a full intervening variable and can mediate the effect of service quality on satisfaction as a partial intervening variable. Suggestions are given so that PT TWC Borobudur Prambanan Ratu Boko is expected to be more aggressive in marketing in the form of promotions through advertisements, posters, brochures, pamphlets, and social media. For the quality of services, it is better to review the service of Borobudur Temple in order to improve the quality of service of the officers in serving visitors and controlling in maintaining the existing infrastructure in the Borobudur Temple Tourism Object.